Disputas socioterritoriais no Amapá: conflitos por terra, água e florestas - Roni Mayer Lomba; Alejandro Fabian Schweitzer (Confins)
This article analyzes the socio-territorial conflicts between land-related social movements in the face of large development projects present in the State of Amapá. It is structurally built on the debate of the social struggle strategies of the subjects involved, usually neglected in economic development policies. For this we used statistical data on conflicts and population, carried out qualitative interviews with leaders of social movements and built thematic maps. We concluded that there is an economic project outlined in the state, supported by public policies that benefit large enterprises and, as a consequence, generate the destruction of the traditional territories of the place and the environment.